Dance and Folklore in a Virtual Environment - Simonič, Mojca (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter explores the connections between dance, folklore, and virtual reality (VR), highlighting the role of modern technologies in preserving cultural heritage. Virtual reality provides interactive and immersive platforms for archiving and learning dances, aiding in the preservation of traditions in the digital age. Researchers are developing VR systems, including 3D avatars and motion analysis tools, that allow learners to study traditional dances in innovative ways. Dance in VR extends beyond documentation, incorporating creativity and emotional expression while facilitating the exploration of new forms of dance. Despite current research limitations, VR presents opportunities for global accessibility and the revitalization of folkloric activities. The chapter concludes that VR serves as a critical bridge between tradition and modernity, ensuring that dance remains relevant and appreciated by future generations.